Catalyst for copolymerization of carbon dioxide and epoxy compound as well as preparation method and application of catalyst
By using a composite catalyst supported by lignin with diethyl zinc and yttrifluoroacetate, the existing catalysts have been solved, and the high molecular weight and high ester segment content have been achieved to efficiently prepare polycarbonate with high molecular weight and high ester segment content, which is suitable for a variety of application fields.
Patent Information
- Application Number
- CN202311368028.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-20
- Publication Date
- 2025-04-22
AI Technical Summary
The existing catalysts have high cost and low activity when preparing polycarbonate, resulting in low molecular weight and low ester segment content of polycarbonate.
Using a composite catalyst supported by lignin with diethyl zinc and yttrifluoroacetate, a composite is formed by the reaction of diethyl zinc with lignin and complexing of yttrifluoroacetate to catalyze the terpolymerization of carbon dioxide, epoxy cyclohexane and ethylene oxide.
It has achieved a low-cost and high-active catalytic effect. The weight average molecular weight of the prepared polycarbonate can exceed 110,000, and the ester segment link content can reach more than 91%. It is suitable for biodegradable plastics, food packaging materials, and agricultural mulching films.
Smart Images

Figure CN119859254A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of catalysts, and more specifically to a catalyst for copolymerization of carbon dioxide and epoxides, and a preparation method and application thereof. Background Art
[0002] Aliphatic polycarbonates can be prepared by copolymerization of epoxy compounds and carbon dioxide. The terpolymer of carbon dioxide, cyclohexene oxide and ethylene oxide improves the mechanical and thermal properties of binary copolymer materials and can be widely used in the fields of biodegradable plastics, food packaging materials and agricultural mulch films. As a new type of non-completely petroleum-based plastic, polycarbonate reduces dependence on petroleum resources. In addition, this type of polyester uses carbon dioxide as one of the comonomers. While utilizing greenhouse gases, it also has biodegradable properties and can effectively reduce white pollution. This undoubtedly brings hope to human society in solving the environmental problems caused by petroleum-based plastics.
[0003] Since Inoue et al. adopted diethyl zinc / water catalytic system to catalyze carbon dioxide and epoxy compound reaction to synthesize aliphatic polycarbonate, various catalytic systems that can be used for carbon dioxide and epoxy compound reaction to prepare aliphatic polycarbonate, such as dicarboxylic acid zinc catalyst, metal porphyrin catalyst, double metal cyanide catalyst and rare earth ternary catalyst, have been reported successively. Motika et al. proposed in U.S. Patent (US 5,026,679) that in the presence of organic solvent, catalysts such as zinc glutarate and zinc adipate prepared by reaction of zinc oxide and aliphatic dicarboxylic acid are used to catalyze the copolymerization of carbon dioxide and propylene oxide, but the molecular weight of the obtained polymer is low, and the activity period of this type of catalyst is short. Kruper et al. have developed chromium metal porphyrin catalyst, which needs to add 4-10 times of nitrogen-containing electron donor (such as methylimidazole and 4-dimethylaminopyridine) cocatalyst to initiate the reaction. Such catalyst can well catalyze carbon dioxide and cyclohexene oxide copolymerization, but it can only obtain cyclic carbonate when catalyzing carbon dioxide and propylene oxide reaction (J.Org.Chem.1995,26,725-727.). Double metal cyanide catalyst is the first to be developed by Kruper and Smart and used for carbon dioxide and epoxy compound polymerization class catalyst, although it has higher monomer conversion when catalyzing carbon dioxide and propylene oxide copolymerization, it is easy to have implosion phenomenon in reaction process, reaction degree is difficult to control, and ether content is too high in its high molecular polymer product, which has a strong impact on the environmental degradability of its products (US4,500,704). People such as Mao Guoyu adopt rare earth compound, glycerine and alkyl zinc as catalyst of carbon dioxide and epoxy compound copolymerization, wherein rare earth compound uses rare earth oxide and chloroacetic acid as raw material to make, catalyst specific surface area is larger, activity is higher, is one of the earliest catalysts applied to industrialization, but this type of catalyst rare earth element consumption is larger, separation and purification is inconvenient, so that production cost is higher (CN1895775A).
[0004] Therefore, how to improve existing catalysts, develop and prepare low-cost, high-activity catalysts, and synthesize high-molecular-weight, high-ester-content aliphatic polycarbonates is the focus of current research. Summary of the invention
[0005] The object of the present invention is to provide a catalyst for the copolymerization of carbon dioxide and epoxy compounds, and a preparation method and application thereof, so as to solve the technical problems in the prior art of preparing polycarbonate that the catalyst cost is high, the activity is low, the molecular weight of the prepared polycarbonate is low, and the ester segment content is low.
[0006] To achieve the above object, the technical solution adopted by the present invention is:
[0007] In a first aspect, the present invention provides a catalyst for the copolymerization of carbon dioxide and an epoxide, which is a composite catalyst of lignin-loaded diethylzinc and yttrium trifluoroacetate.
[0008] The catalyst provided by the invention is a compound formed by the reaction of diethyl zinc with hydroxyl groups on lignin and then complexing with yttrium trifluoroacetate, which can be applied to the ternary copolymerization of carbon dioxide, cyclohexene oxide and ethylene oxide to prepare polycarbonate.
[0009] According to some embodiments of the present invention, the molar ratio of diethyl zinc to lignin is 1:(10-30), and the molar ratio of yttrium trifluoroacetate to lignin is 1:(0.5-4). For example, the molar ratio of diethyl zinc to lignin can be 1:10, 1:15, 1:20, 1:25, 1:30, etc. The molar ratio of yttrium trifluoroacetate to lignin can be 1:0.5, 1:1, 1:2, 1:3, 1:4, 3:4, etc.
[0010] In the present invention, the lignin used generally has a number average molecular weight in the range of 2500-4000.
[0011] In a second aspect, the present invention provides a method for preparing the above catalyst, comprising:
[0012] In a nitrogen atmosphere, yttrium trifluoroacetate, lignin, diethyl zinc and a solvent are mixed and stirred, and then concentrated to obtain the catalyst.
[0013] According to some embodiments of the present invention, the molar ratio of diethyl zinc to lignin is 1:(10-30), and the molar ratio of yttrium trifluoroacetate to lignin is 1:(0.5-4). For example, the molar ratio of diethyl zinc to lignin can be 1:10, 1:15, 1:20, 1:25, 1:30, etc. The molar ratio of yttrium trifluoroacetate to lignin can be 1:0.5, 1:1, 1:2, 1:3, 1:4, 3:4, etc.
[0014] According to some embodiments of the present invention, the ratio of diethyl zinc to solvent is 1 mmol: (2-6) mL. For example, the ratio of diethyl zinc to solvent can be 1 mmol: 2 mL, 1 mmol: 3 mL, 1 mmol: 4 mL, 1 mmol: 5 mL, 1 mmol: 6 mL, etc.
[0015] According to some embodiments of the present invention, the solvent is at least one of tetrahydrofuran, n-hexane, toluene, dichloromethane, and ethyl acetate.
[0016] According to some embodiments of the present invention, the mixing and stirring temperature is 30-70°C, for example, 30°C, 40°C, 50°C, 60°C, 70°C, etc.; the time is 1-5 hours, for example, 1 hour, 2 hours, 3 hours, 4 hours, 5 hours, etc.
[0017] In a third aspect, the present invention provides use of the above catalyst or the catalyst prepared by the above preparation method in catalyzing the terpolymerization of carbon dioxide, cyclohexene oxide and ethylene oxide to prepare polycarbonate.
[0018] In a fourth aspect, the present invention provides a method for preparing polycarbonate by copolymerizing carbon dioxide and an epoxy compound, comprising:
[0019] In a nitrogen atmosphere, the catalyst according to any one of claims 1-2 or the catalyst prepared by the preparation method according to any one of claims 3-5, cyclohexene oxide, ethylene oxide and a solvent are mixed, carbon dioxide is introduced, and the reaction is stirred to prepare polycarbonate.
[0020] According to some embodiments of the present invention, the molar ratio of ethylene oxide to cyclohexene oxide is 1:
[0021] (1-5), the molar ratio of diethyl zinc to cyclohexene oxide is 1:(10-30). For example, the molar ratio of ethylene oxide to cyclohexene oxide can be 1:1, 1:2, 1:2.5, 1:3, 1:4, 1:5, etc. The molar ratio of diethyl zinc to cyclohexene oxide can be 1:10, 1:15, 1:20, 1:25, 1:30, etc.
[0022] According to some embodiments of the present invention, the usage ratio of cyclohexene oxide to solvent is 0.1 mol:
[0023] (20-80) mL. For example, the usage ratio of cyclohexene oxide to the solvent can be 0.1 mol: 20 mL, 0.1 mol: 30 mL, 0.1 mol: 40 mL, 0.1 mol: 50 mL, 0.1 mol: 60 mL, 0.1 mol: 70 mL, 0.1 mol: 80 mL, 0.3 mol: 160 mL, etc.
[0024] According to some embodiments of the present invention, the solvent is at least one of tetrahydrofuran, n-hexane, toluene, dichloromethane, and ethyl acetate.
[0025] According to some embodiments of the present invention, the reaction pressure of the stirring reaction is 2-5 MPa, for example, 2 MPa, 3 MPa, 3.5 MPa, 4 MPa, 5 MPa, etc.
[0026] According to some embodiments of the present invention, the stirring reaction temperature is 60-80°C, for example, 60°C, 70°C, 80°C, etc.; the time is 6-12 hours, for example, 6 hours, 7 hours, 8 hours, 10 hours, 12 hours, etc.
[0027] In a fifth aspect, the present invention provides a polycarbonate prepared by the above method for preparing polycarbonate.
[0028] In a sixth aspect, the present invention provides polycarbonate prepared by the above method or use of the above polycarbonate in the fields of biodegradable plastics, food packaging materials and agricultural mulch films.
[0029] The beneficial effects of the present invention are at least:
[0030] The catalyst provided by the present invention has a wide source of raw materials, a simple preparation method, low cost, high catalytic efficiency, and convenient separation and recovery. It has good catalytic activity for catalyzing the terpolymerization of carbon dioxide, cyclohexene oxide and ethylene oxide. The prepared polycarbonate has a weight-average molecular weight of more than 110,000 and an ester segment content of more than 91%. It can be applied to the fields of biodegradable plastics, food packaging materials and agricultural mulch films. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 Schematic diagram of powder diffraction of the catalyst of Example 1;
[0032] Figure 2 is a scanning electron microscope schematic diagram of the catalyst of Example 1;
[0033] Figure 3 is a schematic diagram of a hydrogen nuclear magnetic resonance spectrum of the polycarbonate of Example 10;
[0034] Figure 4 Schematic diagram of the thermogravimetric analysis of the catalyst. DETAILED DESCRIPTION
[0035] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present invention more clearly understood, the present invention is further described in detail below in conjunction with specific embodiments. It should be understood that the specific embodiments described herein are only used to explain this patent in detail and do not limit the scope of protection of the present invention in any way.
[0036] Unless otherwise defined, the technical terms used in the following examples have the same meanings as those generally understood by those skilled in the art to which the present invention belongs. The reagents used in the following examples, unless otherwise specified, are all conventional biochemical reagents; the raw materials, instruments and equipment used in the following examples, etc., can all be purchased on the market or can be obtained by existing methods; the reagent amounts, unless otherwise specified, are the reagent amounts used in conventional experimental operations; the experimental methods, unless otherwise specified, are all conventional methods.
[0037] The number average molecular weight of the lignin used in the following examples and related test experiments is 3200.
[0038] Example 1
[0039] Under a nitrogen atmosphere, 5 mmol of diethyl zinc, 75 mmol of yttrium trifluoroacetate, 100 mmol of lignin and 20 mL of tetrahydrofuran were added into a closed reactor with magnetic stirring, stirred at 50° C. for 3 hours, and concentrated by distillation to obtain a catalyst for the copolymerization of carbon dioxide and epoxides.
[0040] (1) The structure of the catalyst prepared in this example was determined.
[0041] The X-ray diffraction peak intensity and position were used to analyze the characteristic peaks of lignin before and after loading diethylzinc and yttrium trifluoroacetate. Figure 1 As shown (Instrument model: Rigaku D / Max-2500).
[0042] Since diethyl zinc reacts with chitin to generate -Zn-O- structural units, the X-ray diffraction peaks are used to compare the structure of the catalyst and the structure of the carrier chitin. Figure 1 As shown, the characteristic diffraction peak of lignin is at 22.5°, the diffraction peaks at 31.6°, 34.6° and 36.4° correspond to the (100), (002) and (101) crystal planes of zinc oxide, respectively, and the diffraction peaks at 47.8° and 56.3° correspond to the (440) and (622) crystal planes of yttrium oxide, respectively. This shows that lignin has been loaded with diethylzinc and yttrium trifluoroacetate, which provides a guarantee for its application as a catalyst for the terpolymerization of carbon dioxide, cyclohexene oxide and ethylene oxide.
[0043] (2) The surface morphology of the catalyst prepared in this example was characterized.
[0044] The surface morphology of the catalyst was characterized by field emission scanning electron microscopy (instrument model: ZEISS SUPRA55). Figure 2 As shown in the figure, the surface is smooth before lignin is loaded, but the surface morphology changes significantly after lignin is loaded, and small particles are loaded on the surface.
[0045] Example 2
[0046] Under a nitrogen atmosphere, 5 mmol of diethyl zinc, 100 mmol of yttrium trifluoroacetate, 50 mmol of lignin and 10 mL of tetrahydrofuran were added into a closed reactor with magnetic stirring, stirred at 30° C. for 3 hours, and concentrated by distillation to obtain a catalyst for the copolymerization of carbon dioxide and epoxides.
[0047] Example 3
[0048] Under nitrogen atmosphere, 5 mmol diethyl zinc, 75 mmol yttrium trifluoroacetate, 150 mmol lignin and 30 mL tetrahydrofuran were added into a closed reactor with magnetic stirring, stirred at 50° C. for 1 hour, and concentrated by distillation to obtain a composite catalyst for copolymerization of carbon dioxide and epoxides.
[0049] Example 4
[0050] Under a nitrogen atmosphere, 5 mmol of diethyl zinc, 100 mmol of yttrium trifluoroacetate, 100 mmol of lignin and 20 mL of tetrahydrofuran were added into a closed reactor with magnetic stirring, stirred at 50° C. for 3 hours, and concentrated by distillation to obtain a catalyst for the copolymerization of carbon dioxide and epoxides.
[0051] Experimental Example 5
[0052] Under a nitrogen atmosphere, 5 mmol of diethyl zinc, 25 mmol of yttrium trifluoroacetate, 100 mmol of lignin and 20 mL of tetrahydrofuran were added into a closed reactor with magnetic stirring, stirred at 70° C. for 5 hours, and concentrated by distillation to obtain a catalyst for the copolymerization of carbon dioxide and epoxides.
[0053] Example 6
[0054] Under a nitrogen atmosphere, 5 mmol of diethyl zinc, 75 mmol of yttrium trifluoroacetate, 100 mmol of lignin and 20 mL of n-hexane were added into a closed reactor with magnetic stirring, stirred at 50° C. for 3 hours, and concentrated by distillation to obtain a catalyst for the copolymerization of carbon dioxide and epoxides.
[0055] Example 7
[0056] Under a nitrogen atmosphere, 5 mmol of diethyl zinc, 75 mmol of yttrium trifluoroacetate, 100 mmol of lignin and 20 mL of toluene were added into a closed reactor with magnetic stirring, stirred at 50° C. for 3 hours, and concentrated by distillation to obtain a catalyst for the copolymerization of carbon dioxide and epoxides.
[0057] Example 8
[0058] Under a nitrogen atmosphere, 5 mmol of diethyl zinc, 75 mmol of yttrium trifluoroacetate, 100 mmol of lignin and 20 mL of dichloromethane were added into a closed reactor with magnetic stirring, stirred at 50° C. for 3 hours, and concentrated by distillation to obtain a catalyst for the copolymerization of carbon dioxide and epoxides.
[0059] Example 9
[0060] Under a nitrogen atmosphere, 5 mmol of diethyl zinc, 75 mmol of yttrium trifluoroacetate, 100 mmol of lignin and 20 mL of ethyl acetate were added into a closed reactor with magnetic stirring, stirred at 50° C. for 3 hours, and concentrated by distillation to obtain a catalyst for the copolymerization of carbon dioxide and epoxides.
[0061] Experimental Example 10
[0062] The catalyst prepared in Example 1, 40 mmol of ethylene oxide, 100 mmol of cyclohexene oxide and 50 mL of tetrahydrofuran were added to a dry 300 ml high-pressure reactor, carbon dioxide was introduced, the pressure was adjusted to 3.5 MPa, and the reaction was stirred at 70° C. for 8 hours. The catalyst was filtered and recovered, and 500 mL of methanol was added to the filtrate to precipitate the polymer, which was dried in a vacuum at 50° C. to obtain a white product polycarbonate with a yield of 62%.
[0063] Experimental Example 11
[0064] The catalyst prepared in Example 1, 20 mmol of ethylene oxide, 100 mmol of cyclohexene oxide and 20 mL of tetrahydrofuran were added to a dry 300 ml high-pressure reactor, carbon dioxide was introduced, the pressure was adjusted to 5 MPa, and the reaction was stirred at 70° C. for 12 hours. The catalyst was filtered and recovered, and 500 mL of methanol was added to the filtrate to precipitate the polymer, which was dried in a vacuum at 50° C. to obtain a white product polycarbonate with a yield of 47%.
[0065] Experimental Example 12
[0066] The catalyst prepared in Example 1, 50 mmol of ethylene oxide, 50 mmol of cyclohexene oxide and 20 mL of tetrahydrofuran were added to a dry 300 ml high-pressure reactor, carbon dioxide was introduced, the pressure was adjusted to 2 MPa, and the reaction was stirred at 80° C. for 6 hours. The catalyst was filtered and recovered, and 500 mL of methanol was added to the filtrate to precipitate the polymer, which was dried in a vacuum at 50° C. to obtain a white product polycarbonate with a yield of 43%.
[0067] Experimental Example 13
[0068] The catalyst prepared in Example 1, 60 mmol of ethylene oxide, 150 mmol of cyclohexene oxide and 80 mL of tetrahydrofuran were added to a dry 300 ml high-pressure reactor, carbon dioxide was introduced, the pressure was adjusted to 3.5 MPa, and the reaction was stirred at 60° C. for 8 hours. The catalyst was filtered and recovered, and 500 mL of methanol was added to the filtrate to precipitate the polymer, which was dried in a vacuum at 50° C. to obtain a white product polycarbonate with a yield of 56%.
[0069] Experimental Example 14
[0070] The preparation method of polycarbonate is the same as that of Example 10, except that 50 mL of tetrahydrofuran is replaced by 50 mL of n-hexane.
[0071] Experimental Example 15
[0072] The preparation method of polycarbonate is the same as that of Example 10, except that 50 mL of tetrahydrofuran is replaced by 50 mL of toluene.
[0073] Experimental Example 16
[0074] The preparation method of polycarbonate is the same as that of Example 10, except that 50 mL of tetrahydrofuran is replaced by 50 mL of dichloromethane.
[0075] Experimental Example 17
[0076] The preparation method of polycarbonate is the same as that of Example 10, except that 50 mL of tetrahydrofuran is replaced by 50 mL of ethyl acetate
[0077] Experimental Example 18
[0078] The catalyst prepared in Example 2 was used to prepare polycarbonate, and the preparation method was the same as that in Example 10.
[0079] Experimental Example 19
[0080] The catalyst prepared in Example 3 was used to prepare polycarbonate, and the preparation method was the same as that in Example 10.
[0081] Experimental Example 20
[0082] The catalyst prepared in Example 4 was used to prepare polycarbonate, and the preparation method was the same as that in Example 10.
[0083] Experimental Example 21
[0084] The catalyst prepared in Example 5 was used to prepare polycarbonate, and the preparation method was the same as that in Example 10.
[0085] Experimental Example 22
[0086] The catalyst prepared in Example 6 was used to prepare polycarbonate, and the preparation method was the same as that in Example 10.
[0087] Experimental Example 23
[0088] The catalyst prepared in Example 7 was used to prepare polycarbonate, and the preparation method was the same as that in Example 10.
[0089] Experimental Example 24
[0090] The catalyst prepared in Example 8 was used to prepare polycarbonate, and the preparation method was the same as that in Example 10.
[0091] Experimental Example 25
[0092] The catalyst prepared in Example 9 was used to prepare polycarbonate, and the preparation method was the same as that in Example 10.
[0093] Determination of molecular weight and ester content of polycarbonate
[0094] The molecular weight and ester segment content of the polycarbonate obtained in Examples 10-25 were determined as follows:
[0095] (1) Method for determining weight average molecular weight of polycarbonate
[0096] Take 5.0 mg of polycarbonate, dissolve it in 1 mL of tetrahydrofuran solution, filter it through a polytetrafluoroethylene filter membrane with a pore size of 0.4 microns, take 20 mL and add it to the "LC-20AD GPC" injector made by Shimadzu (Japan), and calculate the weight average molecular weight.
[0097] Test conditions:
[0098] Column temperature: 40°C;
[0099] Eluent: tetrahydrofuran;
[0100] Flow rate: 0.6 mL / min;
[0101] Detector: RID-10A detector;
[0102] Calibration: Molecular weight calibration was performed using four different polystyrene standards with molecular weights ranging from 2000 to 500000.
[0103] (2) Determination of ester content in polycarbonate
[0104] The AVANCE III 500M NMR instrument from Bruker, Germany, was used, with an operating frequency of 400 MHz ( 1H NMR); ultra-super shielded magnet, magnetic field strength 9.4T; equipped with a positive broadband liquid probe, detection range: 1H, 15N-31P; 1H sensitivity ≥300:1 (0.1% EB), 13C sensitivity ≥170:1 (ASTM). Deuterated chloroform is used as solvent, and the ester segment content, epoxy cyclohexane ester content, and ethylene oxide ester content are calculated. Among them, the test results of Example 10 are as follows Figure 3 shown.
[0105] The test results are shown in Table 1:
[0106] Table 1 Polycarbonate performance test results
[0107]
[0108]
[0109] Evaluation of the effect of the amount of diethylzinc added to the catalyst on the catalytic activity
[0110] Different catalysts were prepared by referring to the preparation method of Example 1, except that only the amount of diethyl zinc was changed. Polycarbonate was prepared by using the prepared catalysts according to the method of Example 10, and the weight average molecular weight, molecular weight distribution and ester segment content of the polycarbonate were measured. The results are shown in Table 2.
[0111] Table 2 Effect of the amount of diethyl zinc added to the catalyst on the catalytic activity
[0112]
[0113] As shown in Table 2, when the dosage of lignin is 100mmol and the dosage of yttrium trifluoroacetate is 75mmol, the dosage of diethyl zinc is 5mmol, which is more appropriate. This is because when the content of diethyl zinc is low, the catalytic activity is low due to the small number of active sites (-Zn-O-) for the combination of lignin and diethyl zinc. As the content of diethyl zinc increases, the catalytic activity gradually increases. When the dosage ratio of diethyl zinc to lignin is 1:20, the activity of the catalyst is better.
[0114] Evaluation of the effect of catalyst support types on the mechanical properties of polycarbonate
[0115] Referring to the preparation method of Example 1, only the type of carrier (lignin, chitin, alumina, activated carbon, hydrotalcite) was changed to prepare different catalysts. The prepared catalysts were used to prepare polycarbonate according to the method of Example 10, and the mechanical properties of the polycarbonate were measured. The results are shown in Table 2.
[0116] The mechanical properties were determined as follows:
[0117] According to the ISO527-2 standard, the polymer sample was made into a standard test specimen by a mini injection molding machine (HAAKE Minijet), and the injection temperature was set to 180°C, the pressure was 400 bar, the retention pressure was 350 bar, the injection time was 7 s, and the retention time was 5 s.
[0118] According to GB / T1040-92 standard, the mechanical properties were measured at room temperature and a tensile speed of 20 mm / min. The test data included tensile strength, elastic modulus, elongation at break, etc. Each sample was measured 5 times and the average value was taken.
[0119] Table 3 Mechanical properties of polymers prepared by catalysts supported on different carriers
[0120]
[0121] It can be seen from Table 3 that the polycarbonate prepared by the catalyst using lignin as the carrier has the best mechanical properties, which is closely related to its higher molecular weight and ester segment content, as well as narrower molecular weight distribution.
[0122] Evaluation of the effect of catalyst support type on catalyst thermal stability
[0123] Referring to the preparation method of Example 1, only the type of carrier (lignin, chitin, chitosan) was changed to prepare different catalysts.
[0124] Using the Exstar 6000 thermogravimetric analyzer of Seiko, Japan, 5-10 mg of the above catalysts were placed in a clean Al2O3 crucible, N2 atmosphere, heating rate 10℃ / min, temperature range 30~600℃. The weight loss was measured, and the results were as follows: Figure 4 The test results show that the catalyst using lignin as a carrier provided by the present invention has good thermal stability.
[0125] Evaluation of the Effect of Catalyst Support Type on the Residual Metal Content in Polycarbonate
[0126] Referring to the preparation method of Example 1, only the type of carrier (lignin, chitin, alumina, activated carbon, hydrotalcite) or no carrier (only glycerol) was added to prepare different catalysts. The prepared catalysts were used to prepare polycarbonate according to the method of Example 10, and the metal residue in the polycarbonate was measured. The results are shown in Table 3.
[0127] The method for determining metal residue is as follows:
[0128] Take 10g of polycarbonate and put it into a 100mL Al2O3 crucible. After heating it in an electric furnace for complete degradation, put the remaining solid into a muffle furnace and heat it to 800℃ for 4h. Take out the crucible from the muffle furnace, dissolve the residual sample with hydrochloric acid, make the volume to 100mL, and then measure the metal residue by Vista-AX inductively coupled plasma atomic emission spectrometer (ICP-AES) of Varian Corporation of the United States.
[0129] Table 4 Residual metal content in polycarbonate prepared by catalysts supported on different carriers
[0130]
[0131] As shown in Table 4, the content of metal ions in the polycarbonate prepared by the catalyst using lignin as a carrier provided by the present invention is reduced by about 20 times compared with the unsupported catalyst, and is also significantly improved compared with other supported catalysts. This shows that using lignin as a catalyst carrier has a great advantage in reducing metal residues in polymers, can reduce or even avoid acid pollution caused by washing and purification with hydrochloric acid, and has certain industrial utilization value.
[0132] It should be noted that the embodiments described above are only used to explain the present invention and do not constitute any limitation to the present invention. The present invention has been described with reference to typical embodiments, but it should be understood that the words used therein are descriptive and explanatory words, rather than restrictive words. The present invention may be modified as specified within the scope of the claims of the present invention, and the present invention may be revised without departing from the scope and spirit of the present invention. Although the present invention described therein relates to specific methods, materials and embodiments, it does not mean that the present invention is limited to the specific examples disclosed therein, on the contrary, the present invention can be extended to all other methods and applications with the same functions.
Claims
1. A catalyst for the copolymerization of carbon dioxide and an epoxide, characterized in that: The catalyst is a composite catalyst of lignin-supported diethyl zinc and yttrium trifluoroacetate.
2. The catalyst according to claim 1, characterized in that The molar ratio of the diethyl zinc to the lignin is 1:(10-30), and the molar ratio of the yttrium trifluoroacetate to the lignin is 1:(0.5-4).
3. The method for preparing the catalyst according to claim 1 or 2, characterized in that: include: In a nitrogen atmosphere, yttrium trifluoroacetate, lignin, diethyl zinc and a solvent are mixed and stirred, and then concentrated to obtain the catalyst.
4. The method for preparing the catalyst according to claim 3, characterized in that: The molar ratio of diethyl zinc to lignin is 1:(10-30), and the molar ratio of yttrium trifluoroacetate to lignin is 1:(0.5-4); And / or, the usage ratio of diethyl zinc to solvent is 1 mmol: (2-6) mL.
5. The method for preparing the catalyst according to claim 3 or 4, characterized in that: The solvent is at least one of tetrahydrofuran, n-hexane, toluene, dichloromethane, and ethyl acetate; And / or, the mixing and stirring is carried out at a temperature of 30 to 70° C. and for a time of 1 to 5 hours.
6. Use of the catalyst according to any one of claims 1 to 2 or the catalyst prepared by the preparation method according to any one of claims 3 to 5 in catalyzing the terpolymerization of carbon dioxide, cyclohexene oxide and ethylene oxide to prepare polycarbonate.
7. A method for preparing polycarbonate by terpolymerization of carbon dioxide, cyclohexene oxide and ethylene oxide, characterized in that: include: In a nitrogen atmosphere, the catalyst according to any one of claims 1 to 2 or the catalyst prepared by the preparation method according to any one of claims 3 to 5, cyclohexene oxide, ethylene oxide and a solvent are mixed, carbon dioxide is introduced, and the reaction is stirred to obtain a polycarbonate.
8. The method for preparing polycarbonate according to claim 7, characterized in that: The molar ratio of ethylene oxide to cyclohexene oxide is 1:(1-5), and the molar ratio of diethyl zinc to cyclohexene oxide is 1:(10-30); and / or, the usage ratio of the cyclohexene oxide to the solvent is 0.1 mol: (20-80) mL; And / or, the solvent is at least one of tetrahydrofuran, n-hexane, toluene, dichloromethane, and ethyl acetate; And / or, the reaction pressure of the stirring reaction is 2 to 5 MPa; And / or, the stirring reaction is carried out at a temperature of 60 to 80° C. and for a time of 6 to 12 hours.
9. A polycarbonate prepared by the method according to claim 7 or 8.
10. Use of the polycarbonate prepared by the method of claim 7 or 8 or the polycarbonate according to claim 9 in the fields of biodegradable plastics, food packaging materials and agricultural mulch films.
Citation Information
Patent Citations
Industrial preparation of rare-earth ternary catalyst
CN1895775A
Carbon dioxide oxirane copolymers prepared using double metal cyanide complexes
US4500704A
Mixture of dyes for cyan dye donor for thermal color proofing
US5026679A